In Search of the Resilient Sahelian: Reflections on a Fashionable Notion. Issue 2 (1st March 2017) - Lallau, Benoît
Abstract : This paper examines the figure of the "resilient Sahelian" identified or sought by numerous aid actors and funding bodies in West Africa. Does this notion of resilience contribute to something genuinely new, and if so, how? What methodological challenges does it raise? Can it be operationalized? And, above all, which policies does it require us to implement? These questions need to be addressed head‐on if the "resilient Sahelian" is to be more than a poetic metaphor.